Prospective associations between psychosocial work stress, work-privacy conflict, and relationship satisfaction of young parents during the COVID-19 pandemic: The mediating role of symptoms of depression and anger/hostility - Victoria Weise; Verena C. S. Büechl; Judith T. Mack; Susan Garthus-Niegel (PLoS ONE, 2025)
The COVID-19 pandemic changed employment conditions and childcare availability worldwide. This contributed to higher work-related stress among working parents, which in turn may have led to lower relationship satisfaction. This study examined the prospective associations between psychosocial work stress or work-privacy conflict (WPC) and relationship satisfaction among parents of young children during the first year of the COVID-19 pandemic. Further, this study aimed to investigate a potential mediating role of psychological symptoms, i.e., symptoms of depression and anger/hostility, and to determine whether this applies equally to mothers and fathers. Longitudinal data were derived from the German, prospective cohort study DREAMCORONA. Working and cohabiting mothers (n =  138) and fathers (n =  187) completed questionnaires on psychosocial work stress, WPC, and psychological symptoms from May–June 2020 (T1) and on relationship satisfaction from October–December 2020 (T2). Mediation analyses were conducted separately for mothers and fathers, controlling for working from home and number of children. Mediation effects were found only for fathers. Higher levels of psychosocial work stress were associated with higher levels of symptoms of depression, which in turn predicted lower relationship satisfaction. The prospective association between higher paternal WPC and lower relationship satisfaction was mediated by higher symptoms of both depression and anger/hostility. No mediation effects were found for mothers. However, also in mothers, psychosocial work stress was associated with symptoms of depression, whereas WPC was associated with symptoms of both depression and anger/hostility. This study highlights the importance of identifying protective mechanisms for working parents to maintain mental health and satisfying romantic relationships in times of crisis and beyond. To develop targeted prevention approaches, it appears advantageous to continue examining sex differences. Additionally, it is essential to educate working parents about the potential risks associated with work-related stress and to ensure the availability of stable counselling services.